Nuclear receptor 4A1 (NR4A1) antagonists target paraspeckle component 1 (PSPC1) in cancer cells. Issue 1 (26th October 2021) - Mohankumar, Kumaravel; Shrestha, Rupesh; Safe, Stephen
Abstract: Paraspeckles compound 1 (PSPC1) is a multifunctional protein that plays an important role in cancer cells, where PSPC1 is a master regulator of pro‐oncogenic responses that includes activation of TGFβ (TGFβ1),  TGFβ‐dependent EMT, and metastasis. The pro‐oncogenic activities of PSPC1 closely resembled those observed for the orphan nuclear receptor 4A1 (NR4A1, Nur77) and knockdown of NR4A1 decreased expression of PSPC1 in MDA‐MB‐231 breast, H1299 lung, and SNU449 liver cancer cells. Similar results were observed in these same cell lines after treatment with bisindole–derived (CDIMs) NR4A1 antagonists. Moreover, PSPC1‐dependent regulation of TGFβ, genes associated with cancer stem cells and epithelial to mesenchymal transition (EMT) were also downregulated after NR4A1 silencing or treatment of breast, lung, and liver cancer cells with CDIM/NR4A1 antagonists. Results of chromatin immunoprecipitation (ChIP) assays suggest that NR4A1 regulates PSPC1 through interaction with an NBRE sequence in the PSPC1 gene promoter. These results coupled with in vivo studies showing that NR4A1 antagonists inhibit breast tumor growth and downregulate PSPC1 in tumors indicate that the pro‐oncogenic nuclear PSPC1 factor can be targeted by CDIM/NR4A1 antagonists.